Can reference points explain wage rigidity? Experimental evidence - Christian Koch (Journal for Labour Market Research, 2021)
I examine whether reference points can provide an explanation for rigid wages in recessions. Even though a recession provides a good reason to adjust wages downward, workers' perception of a "fair wage" may depend on their previous wage, their reference point. Using a laboratory experiment, I test this idea by varying whether initially concluded contracts-and their stipulated wages-can serve as reference points. My experimental results show that with initial contracts workers punish wage cuts even in recessions, leading to considerable more rigid wages. Surprisingly, this is even true without an "objective" justification to feel entitled to initial contracts.
Keywords: C9; J3; M5; 330; Wage rigidity; Reference points; Gift exchange; Labor contracts; Experiments